Ydre 2.0: An alternative time-spatial approach towards post-monetarism - Per Assmo; Elin Wihlborg (European Regional Science Association (ERSA), 2010)
The post-industrial information society leads to new patterns of societal change. Despite the changes, the conventional monetary market oriented economic view of development is still dominant. However, essential values are often concealed or even excluded in conventional monetary analyses. Rural areas have a possibility to be in the forefront of new alternative routes to achieve sustainable integrated ecological, social and economic development processes that reaches beyond the conventional monetary market. The ambition of this article is thus to reach beyond the conventional urbanized economic norms and monetary values. This article aims to launch the concept of post-monetarism by elaborating and discuss a conceptual model that can contribute to alternative development approaches. The article enhance new alternative political-economic analytical tools and strategies to achieve a sustainable sound integrated socio-, economic-, and ecological development process. Using a time-spatial perspective, building on Hägerstrand's time-geography, the exploration of an alternative post-monetary norm takes off from an in-depth case study in Ydre municipality, Sweden. The empirical work is conducted through a combination of quantitative data collection, and qualitative methods primarily consisting of in-depth field studies/interviews with households. The analysis reveals the interplay between actors and structures in the interaction between people's daily life, and aggregated data of population, economic activities and political structures. Thereby we aim to reach beyond conventional economic rationale and thereby reduce (or even remove) the mismatch between (economic) micro- and macro analyses. The political implications of these potential conceptual tools could be to analyze and value people's everyday norms and activity patterns in different ways, and thereby avoid inadequate stereotyped standard policies towards development.
Keywords: 330